NO DECREASE IN MUSCLE STRENGTH AFTER BOTULINUM NEUROTOXIN-A INJECTION IN CHILDREN WITH CEREBRAL PALSY - Eek, Meta N.; Himmelmann, Kate (Frontiers in Human Neuroscience, 2016)
Spasticity and muscle weakness is common in children with cerebral palsy (CP). Spasticity can be treated with Botulinum Neurotoxin-A (BoNT-A), but this drug has also been reported to induce muscle weakness. Our purpose was to describe the effect on muscle strength in the lower extremities after BoNT-A injections in children with cerebral palsy. A secondary aim was to relate the effect of BoNT-A to gait pattern and range of motion. Twenty children with spastic cerebral palsy were included in the study, eight girls and 12 boys (mean age 7.7 years). All were able to walk without support, but with increased muscle tone interfering with motor function and gait pattern. Sixteen children had unilateral spastic CP and four bilateral spastic CP. Twenty-four legs received injections with BoNT-A in the plantar flexor muscles. The children were tested before treatment, around six weeks after at the peak effect of BoNT-A, and at six months after treatment, with measurement of muscle strength, gait analysis and range of motion. There were no differences in muscle strength in plantar flexors of treated legs at peak effect compared to baseline. Six months after treatment, there was still no change in untreated plantar flexor muscles, but an increasing trend in plantar flexor strength in legs treated with BoNT-A. Parents reported positive effects in all children, graded as: small in three children, moderate in eight, and large in nine children. The gait analysis showed a small improvement in knee extension at initial contact, and there was a small increase in passive range of motion for ankle dorsiflexion. Two children had a period with transient weakness and pain. We found that voluntary force production in plantar flexor muscles did not decrease after BoNT-A, instead there was a trend to increased muscle strength at follow-up. The increase may be explained as an effect of the blocking of involuntary nerve impulses, leading to an opportunity to using and training the muscles with voluntary control. Adequate muscle strength is important for maintaining the ability to walk and knowledge of how a treatment affects muscle strength is useful when selecting interventions.